‘It would not be tolerated in any other profession except medicine’: survey reporting on undergraduates’ exposure to bullying and harassment in their first placement year - Anja Timm (BMJ Open)
Objectives To determine the extent to which undergraduate medical students experience (and/or witness) bullying and harassment during their first year on full-time placements and to compare with new General Medical Council (GMC) evidence on bullying and harassment of doctors in training.Setting A UK university offering medical and nursing undergraduate programmes.Participants 309 medical and nursing undergraduate students with 30–33 weeks’ placement experience (123 medical students and 186 nursing students); overall response rate: 47%.Primary and secondary outcome measures (A) students’ experience of bullying and harassment; (B) witnessing bullying and harassment; (C) actions taken by students; (D) comparison of medical and nursing students’ data.Results Within 8 months of starting clinical placements, a fifth of medical and a quarter of nursing students reported experiencing bullying and harassment. Cohorts differ in the type of exposure reported and in their responses. Whereas some nursing students follow incidences with query and challenge, most medical students acquiesce.Conclusions Bullying and harassment of medical (and nursing) students—as well as witnessing of such incidents—occurs as soon as students enter the clinical environment. This augments evidence published by the GMC in its first report on undermining of doctors in training (December 2013). The data suggest differences between nursing and medical students in how they respond to such incidents.